cis-Dichloridobis[tris(2-methylphenoxy)phosphane-κP]palladium(II) - Anna M. Trzeciak; Izabela Błaszczyk; Andrzej Gniewek (Acta Crystallographica Section E, 2012)
In the title compound, [PdCl2(C21H21O3P)2], the Pd atom adopts a slightly distorted square-planar coordination geometry, with pairs of the equivalent ligands in cis positions. Adjacent molecules are linked by weak C—H...Cl hydrogen bonds. The crystal structure is additionally stabilized by π–π stacking interactions between the aromatic rings [shortest centroid–centroid distance = 3.758 (4) Å].